From green HRM to sustainable business performance: a two-Stage meta-analytic SEM of the mediating role of green innovation - Dedrix Stephenson Bindeeba (21243596) (2025)
This study examines the impact of Green Human Resource Management (GHRM) on Sustainable Business Performance (SBP) through the mediating role of Green Innovation (GI). Using a two stage meta analytic structural equation modeling approach, we synthesize 210 effect sizes from 137 empirical studies across 43 countries and over 167,000 firm observations. Results show that GHRM directly improves economic, environmental, and social performance and strongly predicts GI, which in turn enhances each performance dimension. Mediation analysis confirms that GI partially transmits GHRM’s influence across all three SBP pillars. We integrate Ability–Motivation– Opportunity theory, the Theory of Planned Behavior, and the Resource Based View to explain how human resource practices build capabilities that drive sustainable innovation. These findings provide clear guidance for managers and policymakers in designing HR policies that foster green innovation and support sustainability goals. Other Information Published in: Cogent Business & Management License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1080/23311975.2025.2536678